In the aftermath of an ethical violation: do family firms suffer more than non-family firms and why? - Nyffenegger, Bettina (Journal of business ethics, 2025)
Research indicates that family firms often engender a sense of trustworthiness among stakeholders. However, little is known as to whether this trustworthiness is beneficial or detrimental to family firms in the face of an ethical scandal. Ethical transgressions can profoundly undermine stakeholders' perceptions of a firm’s integrity and benevolence. Our research examines how stakeholders perceive and react to ethical transgressions committed by family firms, as compared to those committed by non-family firms. Drawing upon expectancy violations theory and social identity theory, we theorize that while family firms inherently enjoy a higher degree of trustworthiness, they suffer significantly more in the aftermath of an ethical transgression. Two scenario-based experimental studies support our theorizing, demonstrating that family firms experience a steeper decline in trustworthiness following an ethical transgression than do non-family firms. We uncover the psychological processes behind this finding, revealing that this vulnerability is attributed to heightened stakeholder expectations and pronounced identification with family firms. We empirically show that expectancy violations primarily diminish integrity perceptions, while identity threats degrade benevolence perceptions of family firms. This research broadens the understanding of ethics in family firms, highlighting how their initially perceived trustworthiness may become a double-edged sword during ethical crises.